1976
DOI: 10.1128/aac.9.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cephalosporin Antibiotics on Blood Coagulation and Platelet Function

Abstract: Administration of cephalothin to normal volunteers in maximal doses of 300 mg/kg per day resulted in a combined defect of platelet function and blood coagulation. No such abnormalities were evident after infusion of cefazolin or cephapirin at a maximal dosage of 200 mg/kg per day. The observed thrombocytopathy was similar to but less severe than that induced by carbenicillin or ticarcillin and was not reflected by a prolonged bleeding time test or impaired prothrombin consumption. Moreover, it was not a consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 7 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…The serum tl/2 of moxalactam in patients with normal renal function was similar to that reported in normal volunteers (7). In patients with severe renal failure, the serum t1/2 was approximately 12 h, and serum levels could be maintained between about 20 and 100 ,ug/ml with dosing of 0.5 to 0.75 g every 12 h. Supplemental dosing would be required after each hemodialysis (1 (3)(4)(5)8).…”
Section: Methodsmentioning
confidence: 52%
“…The serum tl/2 of moxalactam in patients with normal renal function was similar to that reported in normal volunteers (7). In patients with severe renal failure, the serum t1/2 was approximately 12 h, and serum levels could be maintained between about 20 and 100 ,ug/ml with dosing of 0.5 to 0.75 g every 12 h. Supplemental dosing would be required after each hemodialysis (1 (3)(4)(5)8).…”
Section: Methodsmentioning
confidence: 52%
“…Pineo and colleagues have suggested that hypoprothrombinemia is a frequent concomitant condition in the malnourished, often severely debilitated population for whom extended-spectrum cephalosporins are most commonly used and that the apparent increased incidence of coagulopathy reflects the selection bias inherent in the use of these agents in patients with a dietary deficiency of vitamin K (21). Others have proposed a direct inhibition of fibrin formation by ,-lactam antibiotics through the inhibition of the final steps of blood coagulation (6,14). Conly and colleagues have recently proposed that the broad antimicrobial spectrum of the newer cephalosporins eliminates the menaquinone-producing bacteria in the intestinal lumen, thereby facilitating the development of vitamin K deficiency and hypoprothrombinemia in hosts already so predisposed because of pre-existing malnutrition and general debilitation (3,22).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms whereby these agents cause this reaction and the actual incidence of hypoprothrombinemia associated with their therapeutic use are controversial (2,12,14; N. V. Bang, A. Dwyer, S. S. Campbell, C. A. Marks, and R. 0.…”
mentioning
confidence: 99%
“…DISCUSSION Antibiotic-induced platelet dysfunction has been reported most frequently with carbenicillin and penicillin (2,4). However, other penicillins and some cephalosporins, including a few of the newer agents (e.g., piperacillin and moxalactam), have been shown to produce platelet dys- function at various concentrations (3,6,8,13,14). The cases presented here suggest that nafcillin can also induce a hemostatic defect attributable to platelet dysfunction.…”
mentioning
confidence: 88%
“…These defects, however, can result in clinically evident bleeding episodes that may be accentuated by the underlying disease of the patients or by other administered drugs. The time course for the appearance of abnormalities in platelet function and of prolonged bleeding time is from 30 min to 3 days after therapy is started (4,11,13), with the maximum defect in platelet function occurring between 1 and 10 days (3,10). The duration of the platelet function abnormalities is variable but may be prolonged in certain individuals.…”
mentioning
confidence: 99%